KONTRIBUSI WANITA NELAYAN TERHADAP PENDAPATAN KELUARGA DI DESA WABULA KECAMATAN WABULA KABUPATEN BUTON - Fitriani Fitriani; Musadar Mappasomba; Suriana Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This study aims to: Knowing (1) The income of fishermen's families in Wabula Village, Wabula District, Buton Regency. (2) The contribution of women fishermen to family income and compare the magnitude of the contribution from fishery and non-fishery in Wabula Village, Wabula District, Buton Regency. (1) This research was conducted in Wabula Village, Wabula District, Buton Regency which was carried out in February- May 2021 with a total of 45 respondents, these respondents were determined by census. Data analysis in this study used a descriptive method which was processed using household income, fishermen's income and the income contribution formula of fishermen women. The results showed (1) the income of the fishermen's family in Wabula Village, Wabula District, Buton Regency who worked as: a) Seafood seller was Rp. 18,124,651/month; b) Processing fish into fish balls Rp 9,091,023/month; c) Processing fish into fish dumplings amounting to Rp. 6,633,265/month; and d) Buton woven fabric maker Rp. 9,965,195/month. (2) The highest contribution of women fishermen in Wabula Village, Wabula District, Buton Regency is obtained from the fishery sector, which is obtained from working as a seller of seafood, processing fish into fish balls, and processing fish into dumplings. Meanwhile, the lowest contribution of fisherwomen in Wabula Village was obtained from the non-fishery sector, namely from the results of fisherwomen working as Buton woven fabric makers.